The vocational English teachers’ personal competence and its implication on teaching and learning process - Mbarep Wicaksono; Ismail Petrus; Soni Mirizon (EduLite: Journal of English Education, Literature and Culture, 2021)
Personal competence is one of the four main competencies that teachers in Indonesia must possess. However, the literature has been still limited on the teacher's personal competence in the EFL context. Therefore, the present study aims to discover the application of vocational English teachers’ personal competence and its implication on the teaching and learning process. To achieve the purpose of this study, a qualitative approach in a form of case study was employed. Two teachers of English consisting of one male and one female teacher participated in this study and shared their stories about the application of their personal competence at the school. A semi-structured interview became the instrument to obtain the data. The findings of this investigation indicated that the personal competence of EFL teachers was revealed from teachers’ obedience towards regulation, the application of their religious values, the way they treat their students, the honesty and model they demonstrated, the teachers’ maturity, wiseness, and assertiveness, the teachers’ work ethic, the teachers’ confidence in carrying out their duties and the pride towards their profession. The study also discussed how the teachers’ personal competence might affect the teaching and learning process.